Thinking and Speaking - Gaddam, Vaibhav (Stance: an international undergraduate philosophy journal, 2022)
Based on Eli Alshanetsky’s work Articulating a Thought, in this paper, I present a reconstructed puzzle involving complex thoughts and a method for how to tackle articulating them. Then, I reconstruct and provide objections to Alshanetsky’s favored view with rationality. I expound on an initially overlooked deflationary view that is arguably much more viable, while also adding a layer of nuance and granularity to the view that affirms its place in solving the puzzle. I reach the conclusion that if articulation is simply a medium for us to express our complex unfinished thoughts, then perhaps it isn’t necessary for us to clarify the thought.